ANALYSES OF INTERNAL LOAD DURING AN ADOLESCENT FEMALE HANDBALL SEASON - Marta Camacho Cardeñosa; Alba Camacho Cardeñosa; Ismael Martínez Guardado; Rafael Timón Andrada; Guillermo Olcina Camacho; Javier Brazo Sayavera (Federación Extremeña de Balonmano; University of Extremadura, 2017)
Abstract This study examined the internal load based on heart rate (HR) in a teenage female handball team, which is playing in a regional league, comparing these parameters between the first and second half of the matches. A total of 10 adolescent female handball players participated in the study (age 14.70 ± 0.67 years (range, 14-15), weight 55.78 ± 6.80 kg (range, 46.70-68.90), height 160.44 ± 8.53 cm (range, 150.00-177.00), BMI 21.60 ± 1.10 kg/m2 (range, 19.90-23.10), fat mass 30.89 ± 3.70 % Fat Mass (range, 24.40-35.60) and VO2max 35.00 ± 1.00 ml·min·kg-1 (range, 33.76-36.00). Heart Rate (n=120) analyses were registered throughout 12 official matches using Heart Rate monitors. Individual demands were categorized into six intensity zones based on % Maximum Heart Rate (HRmax): zone I: 0-50%; zone II: 51-60%; zone III: 61-70%; zone IV: 71-80%, zone V: 81-90 and zone VI: 91-100% of HRmax. Effective maximum and mean Heart Rate in the total match were 204.146.12 and 185.718.33 b·min-1, respectively. During the second half, effective maximum (201.715.23 vs 204.156.57 b·min-1; p=0.001) and effective mean (183.518.61 vs 189.677.47 b·min-1; p=0.000). Heart Rate decreased comparing to the first half. Female adolescent team handball players develop a high intensity during official matches. This intensity is higher in first half compared to the second half.   Resumen Este estudio examina la carga interna basada en la frecuencia cardiaca (FC) durante una liga regional en jugadoras adolescentes de balonmano, comparando estos parámetros entre la primera y la segunda parte del partido. Un total de 10 jugadoras adolescentes de balonmano participaron en este estudio (edad 14,70 ± 0,67 años (rango, 14-15), masa corporal 55,78 ± 6,80 kg (rango, 46,70-68,90), talla 160,44 ± 8,53 cm (rango, 150,00-177,00), IMC 21,60 ± 1,10 kg/m2 (rango, 19,90-23,10), masa grasa 30,89 ± 3,70 % Masa Grasa (rango, 24,40-35,60) y VO2max 35,00 ± 1,00 ml·min·kg-1 (rango, 33,76-36,00)). El análisis de la frecuencia cardíaca (n=120) fue registrado durante 12 partidos oficiales usando monitores de frecuencia cardiaca. Las demandas individuales fueron categorizada en 6 zonas de intensidad basándose en el % Frecuencia Cardíaca Máxima (FCmáx): zona I: 0-50%; zona II: 51-60%; zona III: 61-70%; zona IV: 71-80%, zona V: 81-90 y zona VI: 91-100% de la FCmáx. La FCmáx Efectiva y Media durante el partido fueron 204,146,12 y 185,718,33 ppm, respectivamente. Durante la segunda parte, la frecuencia cardiaca máxima efectiva (201.715.23 vs 204.156.57 ppm; p=0.001) y media efectiva (183.518.61 vs 189.677.47 ppm; p=0.000) decrecieron en comparación con las primeras partes. Las jugadoras de balonmano adolescente desarrollaron una alta intensidad durante partidos oficiales, siendo más alta en la primera parte comparada con la segunda.